The Phenomenon of Corn Invasion into Forest Areas and the Proposal for Land Management in the Northern Highland Forest - มงคลเจริญสกุล สุรพจน์ (Journal of Social Sciences, Chiang Mai University, 2019)
This paper is an attempt to portray the complexity of resource management problem in Northern highland where the phenomenon of corn invasion into forest takes place; and the people’s movement basing on community rights approach as their tool for negotiation on land management in the forest areas. This was drawn by the case study of a Pgaz K’ Nyau community in the highland of Mae Chaem District, Chiang Mai Province in order to reflect the change of modes of production and consumption into cash economy which is closely related to land rights in the highland. This leads to the proposal for joint resource management being driven by the local people in order to adjust relationship in terms of power structure between the people who grow corn on land with no land title and the government agencies. In addition, it also aims to illustrate the expansion of corn fields into forest areas through the analysis of the informal clientele of farmers to corporate patron and the concept of highland resource management.